2010
DOI: 10.1007/s00253-010-2484-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the biocompatibile ionic liquid 1-methyl-3-methylimidazolium dimethylphosphite pretreatment of corn cob for improved saccharification

Abstract: Ionic liquid (IL) pretreatment of lignocellulose materials is a promising process in biomass conversion to renewable biofuel. More in-depth research involving environment-friendly IL is much needed to explore pretreatment green route. In our case, IL 1-methyl-3-methylimidazolium dimethylphosphite ([Mmim]DMP) was chosen as an environment-friendly solvent to pretreat corn cob in view of its biocompatibility with both lignocellulose solubility and cellulase activity. The pretreatment/saccharification process and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…Some ILs are powerful solvents for lignocellulosic materials, which can dissolve cellulose or lignocellulosic biomass forming homogeneous solutions (Zavrel et al, 2009). Li et al (2010) investigated the effect of various ILs pretreatment on enzymatic hydrolysis of corn cob. It was found that ILs containing phosphate or chloride groups enhanced the yield of reducing sugar significantly.…”
Section: Ionic Liquids (Ils) Pretreatmentmentioning
confidence: 99%
“…Some ILs are powerful solvents for lignocellulosic materials, which can dissolve cellulose or lignocellulosic biomass forming homogeneous solutions (Zavrel et al, 2009). Li et al (2010) investigated the effect of various ILs pretreatment on enzymatic hydrolysis of corn cob. It was found that ILs containing phosphate or chloride groups enhanced the yield of reducing sugar significantly.…”
Section: Ionic Liquids (Ils) Pretreatmentmentioning
confidence: 99%
“…Recently, pretreatment with ionic liquids (ILs) has been received intensive study (KleinMarcuschamer et al, 2011), and more biocompatible ILs have been developed. Regardless of detailed procedures (Li et al, 2010;Ninomiya et al, 2012;Wang et al, 2011), however, ILs are carried over and present at various concentrations in the stream used for fermentation ). This may cause unacceptable effects.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, the applications of microwave radiation were limited to the digestion of samples for measuring trace metals (Huffer et al, 1998) and extraction of organic contaminants (Marcato and Vianello, 2000). The feasibility of extracting lipids using microwave irradiation was first reported in the mid-1980s (Ganzler et al, 1986).…”
Section: Microwavementioning
confidence: 99%